Mobile Assisted Language Learning (Mall) In English Teaching And Learning Process Ona Descriptive Study - Putri, Melinda (Universitas Muhammadiyah Sumatera Utara, 2021)
This research deals with the use of mobile phone in English teaching andlearning process at FKIP UMSU. The objective of this research is to find outstudents perceptions about the use of MobilePhonein English teaching andlearning process and to describe how do students use mobile phone in English teaching and learning process. The research was descriptive qualitative research. The data collected by interviewing 20 students. In this study the researcher collected the data by using interview that consist five question. The findings that students had different perceptions, namely: mobile phone is very help ful in English teaching and learning process, mobile phone is important in English teaching and learning process and mobile phone has advantages and disadvantages. In Englsih teaching and learning process, studentstake advantage of their mobile phone by using several applications, including:Google Translate, WhatsApp, Google Classroom, Gmail, U-Dictionary, Google,Camscanner, Oxford Dictionary of English, English Thesaurus, English Grammar,Irregular and Regular Verb,Offline Dictionary,My Dictionary.